(untitled) (Web of Teachers: Inderscience Research, 2026)
This study examines the distinction between semantics and pragmatics through Geoffrey Leech’s theoretical framework presented in Principles of Pragmatics. The research focuses on two central propositions: first, that semantic representation is distinct from pragmatic interpretation, and second, that semantics is rule-governed while pragmatics is principle-controlled. Using qualitative theoretical analysis, the study investigates Leech’s critique of the performative hypothesis and speech act theory, particularly their limitations in explaining natural communication. The findings demonstrate that semantic meaning cannot fully account for speaker intention, contextual inference, and multifunctional utterances. Likewise, purely pragmatic models such as speech act theory oversimplify communication by reducing language to discrete action categories. The analysis confirms that semantics provides the structural basis for meaning, whereas pragmatics explains how speakers use language flexibly according to communicative goals and contextual factors. The study concludes that maintaining the analytical distinction between semantics and pragmatics offers a more comprehensive model for understanding natural language use.